Pengukuran Kesiapan Transformasi Digital Desa Kaduwulung Menuju Desa Cerdas Berbasis SNI ISO 37122:2019 Melalui Pemetaan Data Desa - Firmansyah, Esa; Agreindra Helmiawan, Muhammad (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2025)
This study measures the readiness of digital transformation in Kaduwulung Village towards becoming a smart village using the SNI ISO 37122:2019 framework through information technology-based village data mapping. A quantitative method was applied by collecting data from 19 sectors and 81 standard indicators, which were then analyzed to determine the level of maturity. The results indicate a readiness achievement level of 52.4%, with key supporting factors including the availability of telecommunication infrastructure and support from the local government. Meanwhile, the main obstacles identified were limited inter-agency coordination, low digital literacy among citizens, and budget allocation constraints. GIS-based data mapping proved effective in identifying implementation gaps.